HUBUNGAN PENGETAHUAN IBU MENYUSUI DENGAN PERILAKU PEMBERIAN ASI EKSKLUSIF DI POLIKLINIK TUMBUH KEMBANG RSUP.DR.SARDJITO YOGYAKARTA - Frederika N.M. Lossu; Widayawati Widayawati; Fitri Haryanti (POLTEKKES KEMENKES MANADO, 2014)
The exclusive breastfeeding is a relative new science, it also be learned especially bymothers because appearance of Indonesian female was very bad classify. Principally ofDistrict Statistic Center, 1997 that 8 of 100 female have illiteracy were compared with 3 of 100male in cities.The objectives of this research to find out the relation between mother's knowledge lactation andgiven behaviour exclusive breastfeeding in development and growth blinic of RSU. Dr. SardjitoYogyakarta.This was a survey descriptive with cross sectional approach.The implementation ofresearch at 1st until 2ndweeks on July 2002. Thirty mothers lactation have baby at 4 until 12month were participated in this research.Statistical results with used product moment formula showed correlation (r) = 0,526 withsignifican 0,003, it means there was middle possitive relation between mother 'sknowledge lactation and given behaviour exclusive breastfeeding in development andgrowth clinic of RSU. Dr. Sardjito Yogyakarta.